Acceptability of COVID-19 vaccine among medical students: a cross-sectional analysis - G. R., Leela; R., Pandurangaiah; C. K., Rajamma (International Journal of Advances in Medicine, 2021)
Background: After the announcement of vaccine in India for health care worker, medical students is one among them, they are exposed to the COVID-19 patients. Vaccination plays crucial role in controlling the pandemic, study to know the acceptability of vaccine. Methods: Total of 1030 medical students are enrolled in the prospective cross-section study done in Kerala. Online Questionnaire was filled between 1st January 2020 to 28th February 2021 and data collected and analysed. Results: Out of 1030 students we found that high rate of acceptability, 710 (67%) of students willingness to take vaccine if eligible. Females (73%) are more willing to accept vaccine then male (65%), students as good knowledge, attitude and practice towards COVID-19. Conclusions: As these students are come in health care worker we need to cover 100% vaccination in them this will be the direct impact on the general population. Increase awareness of medical college students about current available vaccine to reduce hesitancy.